New prenyllipid metabolites identified in Arabidopsis during photo‐oxidative stress. (30th June 2015) - Dłużewska, Jolanta; Zieliński, Kamil; Nowicka, Beatrycze; Szymańska, Renata; Kruk, Jerzy
Abstract: In the present study, we have identified new prenyllipid metabolites formed during high light stress in A rabidopsis thaliana, whose origin and function remained unknown so far. It was found that plastoquinone‐C accumulates mainly in the reduced form under high light conditions, as well as during short‐term excess light illumination both in the wild‐type and tocopherol biosynthetic vte1 mutant, suggesting that plastoquinone‐C, a singlet oxygen‐derived prenyllipid, is reduced in chloroplasts by photosystem II or enzymatically, outside thylakoids. Plastoquinone‐B, a fatty acid ester of plastoquinone‐C, was identified for the first time in Arabidopsis in high light grown wild‐type plants and during short‐time, excess light illumination of the wild‐type plants and the vte1 mutant. The gene expression analysis showed that vte2 gene is most pronouncedly up‐regulated among the prenyllipid biosynthetic genes under high light and induction of its expression is mainly caused by an increased level of singlet oxygen, as was demonstrated in experiments with D2 O‐treated plants under excess light conditions. Abstract : The aim of the study was to investigate possible new prenyllipid metabolites formed during high light stress in A rabidopsis thaliana and analyze correlation of genes expression involved in prenyllipid biosynthesis with the level of prenyllipids. It was found that plastoquinone‐C accumulates mainly in the reduced form under high light conditions, as well as during short‐term excess light illumination. Plastoquinone‐B, an fatty acid ester of plastoquinone‐C, was identified for the first time in A rabidopsis in high light grown plants and during short‐time, excess light illumination. The gene expression analysis showed that vte2 gene is most pronouncedly up‐regulated among the prenyllipid biosynthetic genes under high light and induction of its expression is mainly caused by an increased level of singlet oxygen.